2015
DOI: 10.3390/s150512092
|View full text |Cite
|
Sign up to set email alerts
|

LED-Absorption-QEPAS Sensor for Biogas Plants

Abstract: A new sensor for methane and carbon dioxide concentration measurements in biogas plants is presented. LEDs in the mid infrared spectral region are implemented as low cost light source. The combination of quartz-enhanced photoacoustic spectroscopy with an absorption path leads to a sensor setup suitable for the harsh application environment. The sensor system contains an electronics unit and the two gas sensors; it was designed to work as standalone device and was tested in a biogas plant for several weeks. Gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 12 publications
0
26
0
7
Order By: Relevance
“…6 A number of different light sources (QCLs, LEDs, DFBs, OPOs and more) have been reported used in QEPAS experiments. [15][16][17][18][19][20] OPOs seem to be the optimal choice for providing large wavelength tunability, high energy, molecular selectivity and cost-effective device for the generation of infrared light in the 1.5 to 5 µm spectral range. 21 Therefore, a pulsed single mode mid-infrared (MIR) OPO has been developed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A number of different light sources (QCLs, LEDs, DFBs, OPOs and more) have been reported used in QEPAS experiments. [15][16][17][18][19][20] OPOs seem to be the optimal choice for providing large wavelength tunability, high energy, molecular selectivity and cost-effective device for the generation of infrared light in the 1.5 to 5 µm spectral range. 21 Therefore, a pulsed single mode mid-infrared (MIR) OPO has been developed.…”
Section: Methodsmentioning
confidence: 99%
“…11 Standard low cost QTFs with resonance frequencies at 32.7 kHz are typically used as sensors, however, also custom made QTFs have been reported. [12][13][14][15][16][17][18] The PA signal is proportional to the Q-factor: S ∝ QP α/f 0 , where P is the optical power, α is the molecular absorption coefficient and f 0 is the resonant frequency of the QTF. The stiffness of quartz provides an efficient means of confining the acoustic energy in the prongs of the QTF, resulting in large quality factors (Q-factors) of the order 100000 in vacuum and 3-8000 at atmospherical pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of the light source leads to the exiting soundwave whose amplitude is related to the amount of target gas in the measurement channel. About a decade ago, the first attempt to miniaturize this simple concept did use a micro-electro-mechanical system pressure sensor to gauge the light intensity of a thermal emitter [22], and since then different combinations of various types of broad band light sources and devices for determining the photoacoustic signal have been developed [23][24][25][26][27][28][29][30][31]. While the use of lasers in combination with acoustic resonators in setups of direct photoacoustic spectroscopy allow for ultra-sensitive trace gas detection, the use of such devices outside the laboratory is challenging [32][33][34][35][36].…”
Section: Practical Applicationmentioning
confidence: 99%
“…Hence, researchers worldwide are trying to meet the demand of devices that can be used to monitor the network condition at reduced cost. Recently, Kö hring et al [2] have shown the feasibility of a light emitting diodebased quartz enhanced photoacoustic sensor for methane and CO 2 detection in biogas plants with fast response time, broad concentration range and low cross sensitivities. However, the sensor showed temperature and pressure dependent signal variations.…”
Section: Introductionmentioning
confidence: 99%